PENERAPAN TEKNOLOGY SPEECH RECOGNITION UNTUK LATIHAN PRONUNCIATION BAHASA INGGRIS MELALUI METODE DICTATION DI PROGRAM STUDI MULTIMEDIA BROADCASTING POLITEKNIK ELEKTRONIKA NEGERI SURABAYA - Aliv Faizal M; Akhmad Alimudin (NJCA (Nusantara Journal of Computers and Its Applications), 2018)
English pronunciation has long been taught through the delivery of phonetic symbols to study the sound of each phoneme in English. In Multimedia Broadcasting study program at Surabaya State Electronics Polytechnic, pronunciation has long been delivered to the students through guidebooks in the form of phonetic symbols that teach basic sound pronunciation in English. English teachers practice the sound of each phoneme directly to thestudents. After going through various observations based on the track record of student achievement of this pronunciation material, I as a teacher as well as researcher found that my student achievement was less than the desired target. This was due to the limited source of English pronunciation learning where students only learned face-to-face in the classroom. Through the use of English learning media of pronunciation interactively using speech recognition technology, it was expected that Multimedia Broadcasting course students in Surabaya State Electronics Polytechnic could improve their English pronunciation ability. After students complete the English pronunciation training sequence using pronunciation application using speech recognition technology, the data from the interview stated that the students felt more confident and improved their pronunciation ability and also felt the increased motivation to learn English pronunciation using English pronunciation learning app using speech recognition technology.Keywords: English pronunciation, teaching, multimedia, speech recognition technology, and pronunciation app.